Bevel Gear Fundamentals and Applications - Klingelnberg, Jan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2016)
This is the first book to offer a complete presentation of bevel gears. An expert team of authors highlights the areas of application for these machine elements and presents the geometrical features of bevel gears as well as the various gear cutting processes based on gear cutting theory. The aspect of three-dimensional gearing is assessed in detail in terms of flank design, load capacity and noise behavior. A representation of production processes with the required technologies provides a knowledge base on which sound decisions can be based. The authors offer a thorough introduction to the complex world of bevel gears and present the rapid advances of these machine elements in a detailed, comprehensible manner.  This book addresses design engineers in mechanical engineering and vehicle manufacturing, as well as producers of bevel gears and students in mechanical engineering.
Fields of application for bevel gears -- Fundamentals of bevel gears -- Design of bevel gears -- Load capacity and efficiency -- Noise behavior -- Manufacturing process -- Quality assurance -- Dynamics of machine tools.
Keywords: Machinery; Engineering design; Manufactures; Machinery and Machine Elements; Engineering Design; Machines, Tools, Processes